ESRA19-0187 Regional anaesthesia in the management of major chest trauma: an audit of current practice in a major trauma centre. (30th August 2019) - Trainer, C; Kowa, CY; Egan, T
Abstract : Background and aims: Rib fractures are a major cause of trauma morbidity and mortality. Analgaesia is paramount, as uncontrolled pain leads to hypoventilation with its attendant complications. Regional anaesthesia (RA) is the standard of care; it is often underutilised. Provided no contraindication, NHS England stipulates that RA is provided within 6 hours of radiological diagnosis. This audit evaluates current practice at a London major trauma centre. Methods: Data were obtained from the Trauma and Audit Research Network database over 3 months commencing October 2018 for patients with ≥3 rib fractures or chest drain. We recorded time from diagnosis to consideration and performance of RA, and qualitative data on choice of analgesia, service delays and complications. Results: 37 patients were admitted; 28/37 male, aged 68.8 yrs (55.6–79.8), ISS 24 (17–34). We excluded 4 patients without valid identifiers; a further 3 had unsurvivable injuries. In 11/30 RA was considered within 6h, rising to 18/30 in total (range 0->140h), with 7/30 eventually receiving RA. In 10/23 epidural/PVB was contraindicated. Some received sequential procedures: initial failure, or single-shot temporization followed by catheter. Reasons for non-provision are documented in figure 1 . In 7/7 patients, RA was delayed >24h from diagnosis. Conclusions: RA considered early in majority of cases; <25% received Adequacy of early pain control often undocumented Risk–benefit documentation lacking for relative contraindications Documented shortage of anaesthetic/theatre capacity in a few (but likely accounts for more) lost–to–RA cases Expanding service capacity and improving out–of–hours provision may help Many have contraindications, suggesting a role for emerging novel chest wall blocks SA/ESP